Design of a pilot control module based in RFID to retails - Inche Mitma, Jorge (2011)
This article focused the next problem: What elements does have a design of a module control in a retail?; to answer this question, proceeded to characterizing an identification system by Radio Frequency (RFID) to buying massive products organizations. The research only shows the design and the general benefits, any economic analyze or rate of return will depends of the enterprise where it applies.